PROBLEMATIKA EKSEKUSI PUTUSAN HARTA BERSAMA DI ATAS TANAH ADAT (STUDI DI DESA LEBAH SEMPAGA KECAMATAN NARMADA KABUPATEN LOMBOK BARAT) - Baiq Santi Sulistiorini (Universitas Islam Negeri (UIN) Mataram, 2019)
This study aims to determine the customary provisions of the Village of Lebah Sempaga regarding the mastery of buildings on customary land, know the legal considerations of the judges and the barriers to execution of shared property on customary land. This research is a field research using normative and sociological juridical approaches and involves judges and litigants, community leaders and traditional leaders of Lebah Sempaga Village. Data mining is done by observation, indepth interviews and documentation studies. The results of this study indicate that the customary provisions of the Lebah Sempaga Village regarding the mastery of buildings on